Controlled perfluorination of poly(2, 3, 4, 5, 6-pentafluorostyrene) (PPFS) and PPFS-functionalized fumed silica by thiol-para-fluoro coupling: Towards the design of self-cleaning (nano)composite films. (May 2018) - Yin, Quanyi; Alcouffe, Pierre; Beyou, Emmanuel; Charlot, Aurélia; Portinha, Daniel
Graphical abstract: Highlights: Perfluorinated thiol used to modify PPFS by controlled thiol-para-fluoro coupling. Surface energy of resulting polymers tuned by degree of substitution (DS) Coupling reaction extended to the perfluorination of PPFS modified silica. Perfluorinated polymers and modified silica combined to prepare nanocomposite films. Specific DS and silica content endow the film with self-cleaning properties. Abstract: Perfluorinated poly(2, 3, 4, 5, 6-pentafluorostyrene) (PPFS) and PPFS-functionalized silica (nano)particles derivatives were synthesized and further combined to prepare organic/inorganic (nano)composite films. First, the post-polymerization modification of PPFS with 1 H, 1 H, 2 H, 2 H -perfluorodecanethiol (PFDT) via a versatile thiol-para-fluoro coupling was optimized to synthesize fluoropolymers PPFS-PFDT with randomly distributed perfluorinated groups, which hydrophobicity was tuned by the degree of substitution (DS). Then, the coupling reaction was successfully applied to the perfluorination of PPFS-functionalized fumed silica. A library of fluorinated polymers (PPFS or PPFS-PFDT with different DS) were combined with modified silica to elaborate multiscale-textured nanocomposite films exhibiting self-cleaning properties.